Description of two new species of ants of the genus Myrmecina Curtis, 1829 (Hymenoptera: Formicidae: Myrmicinae) from the Eastern Himalayas - Aswaj, Punnath; Anoop, Karunakaran; Priyadarsanan, Dharma Rajan (Zootaxa, 2021)
Two new species of the ant genus Myrmecina Curtis, 1829, M. bawai sp. nov. and M. reticulata sp. nov., are described and illustrated based on the worker caste from Mizoram, Northeast India. The genus is reported for the first time from Mizoram, the Indian state with the highest percentage of forest cover. A key to the Indian fauna of Myrmecina is also provided based on the worker caste.